Sacred Maya incense, copal (Protium copal - Burseraceae), has antianxiety effects in animal models. (24th April 2018) - Merali, Zul; Cayer, Christian; Kent, Pamela; Liu, Rui; Cal, Victor; Harris, Cory S.; Arnason, John T.
Abstract: Ethnopharmacological relevance: The Maya have traditionally used copal, Protium copal, as incense during ceremonies since pre-Columbian times. Anecdotally, copal (when burned as incense), is thought to elicit mentally uplifting and calming effects. The main objective of this study was to determine whether the incense elicits anxiolytic-like behavior in animal models using rats. A second objective was to characterize active constituents and discern potential mechanism(s) of action, specifically the involvement of the GABAergic and endocannabinoid (eCB) systems. Despite the extensive Central American use of this resin, there are currently no known scientific behavioral or pharmacological studies done with the incense. Materials and methods: Quantification of the triterpenes in the copal resin and cold trapped incense was achieved by HPLC MS. Behavioral effects in rats were assessed using the elevated plus maze (EPM), social interaction (SI) test, conditioned emotion response (CER) and Novel object recognition (NOR) paradigms. Rats were exposed to burning copal (200 mg) over 5 min in a smoking chamber apparatus and then immediately tested in each behavioral paradigm. Follow-up SI tests were done using two antagonists flumazenil (1 mg/kg) and AM251 (1 mg/kg) administered systemically. Inhibition of MAGL (monoacylglycerol lipase) was measured by microplate assay with recombinant human enzyme and probe substrate. Results: Phytochemical analysis revealed that copal resin and incense had high α- and β-amyrins and low lupeol triterpene content. Exposure to Protium copal incense significantly reduced anxiety-like behavior in the SI and CER tests. In contrast, no anxiolytic effects were observed in the EPM. The CER effect was time dependent. Both flumazenil and AM251 blocked the anxiolytic activity of copal revealing the involvement of GABAergic and endocannabinoid systems. Copal, as well as the identified triterpenes, potently inhibited monoacylglycerol lipase (MAGL) activity in vitro (IC50 ≤ 811 ng/mL). Conclusions: This is the first study to show that copal incense from Protium copal elicits anxiolytic-like effects in fear and social interaction models as evidenced by a reduced learned fear behavior and an increase in active social interaction. It's high α and β-amyrin content suggests behavioral effects may be mediated, in part, by the known action of these terpenes at the benzodiazepine receptor. Furthermore, P. copal 's observed activity through the eCB system via MAGL offers a new potential mechanism underlying the anxiolytic activity. Graphical abstract: Copal incense anti-anxiety effect In animals